2017
DOI: 10.4149/bll_2017_005
|View full text |Cite
|
Sign up to set email alerts
|

Is choroidal thickness related with disease activity and joint damage in patient with rheumatoid arthritis

Abstract: OBJECTIVE: Aim of the study was to evaluate the choroidal thickness (CT) in patients with RA and detect the relation with disease activity and joint damage in patients with rheumatoid arthritis BACKGROUND: Rheumatoid arthritis (RA) is a systemic infl ammatory disease associated with various extraarticular organ manifestations including ocular manifestations MATERIALS AND METHODS: We included 59 eyes of 59 patients with RA and 59 eyes of 59 controls without RA in the study. Subfoveal and perifoveal CT were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In contrast to the Duru et al 's study [130], Kurt et al [132] reported a significantly thinner choroid in patients with active disease than patients in remission. However, consistent with Duru et al 's results, a relationship between activity level and CT has not been shown [132].…”
Section: Vasculitis Associated With Systemic Diseasementioning
confidence: 68%
See 2 more Smart Citations
“…In contrast to the Duru et al 's study [130], Kurt et al [132] reported a significantly thinner choroid in patients with active disease than patients in remission. However, consistent with Duru et al 's results, a relationship between activity level and CT has not been shown [132].…”
Section: Vasculitis Associated With Systemic Diseasementioning
confidence: 68%
“…In contrast to the Duru et al 's study [130], Kurt et al [132] reported a significantly thinner choroid in patients with active disease than patients in remission. However, consistent with Duru et al 's results, a relationship between activity level and CT has not been shown [132]. Contrary to these studies reporting a thinner choroid in RA patients, there is one study showing no difference [133] and another stating a significantly increased CT which was positively correlated with rheumatoid factor [134].…”
Section: Vasculitis Associated With Systemic Diseasementioning
confidence: 68%
See 1 more Smart Citation
“…Kurt et al demonstrated decreased corneal thickness (CT) of 59 RA patients compared to healthy controls. However, no significant correlation was found between CT measurements and Disease Activity Score 28 (DAS 28) or Larsen disease activity scores [8].…”
Section: Choroidmentioning
confidence: 97%
“…Melanin, produced in melanocytes in the choroidal layer and stored in melanosomes, has a crucial role in protecting and absorbing light from intraocular reflection (4). There are a limited number of studies showing that the affected choroid is also affected in vitiligo in some systemic inflammatory diseases (5,7).…”
Section: Introductionmentioning
confidence: 99%